Pertimbangan Hakim Atas Gugatan terkait Objek Jaminan dalam Masa Eksekusi Kreditor Separatis (Studi Putusan Nomor 40/Pdt.Sus-Guagatan Lain-Lain/2019/PN.Niaga.Jkt.Pst) - Boni, Anggara Sinaga; Fauzi, Muhammad; Hediati, Febri Noor (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora; Vol 1 No 1 (2023): Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations has regulated the right to execute collateral held by separatist creditors which must be in accordance with Article 59 paragraph (1) which explains that creditors holding rights must exercise their rights within a period of no later than 2 months and during the execution of the security property are entitled to freedom in carrying out the execution without any interference from any party. This Doctrinal Research is based on the existence of a problem that exists in the Bankruptcy case in Decision Number: 40/Pdt.sus-Other Suit/2019/PN.Niaga.Jkt.Pst. and is guided by the Legislation, especially Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. In the settlement of bankruptcy cases, there are still problems, this is due to the discrepancy between the Judge's decision and the regulations governing the right to execute collateral property carried out by separatist creditors, this can cause harm to one of the litigants in the bankruptcy case settlement process. So this research is needed to analyze the considerations of the Judge in making decisions related to the settlement of bankruptcy cases which must be in accordance with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations.